VISUALISASI EKSPRESI WAJAH DALAM KARYA LUKIS REALIS - DEDE KURNIAWAN, Ir. Drs. Heldi, M.Si., Drs. Abd. Hafiz, M.Pd. (Universitas Negeri Padang, 2016)
This thesis aims to meaning of various human facial expressions into the media of painting through a different perspective in a non-verbal language. Behavior through mind giving motion effects that can be read, the theoretical study of the motion comes as spontaneous thoughts due to certain conditions.Variety of facial expressions which appear in everyday not only be passed or ignored, but after exploration of facial expressions can be appreciated by a work of art that can be enjoyed by many people, so the meaning behind facial expressions can be known through the media of painting, there are 10 tittles of thesis there are: 1. Happiness, 2. Appreciations, 3. Sad, 4. Repugnant, 5. Surprised, 6. Shock, 7. Thinking, 8. Search, 9 tired, and 10. AngryKata Kunci : Mengungkap berbagai makna ekspresi wajah manusia ke dalam media lukis melalui perspektif yang berbeda dalam bahasa rupa.